KEPEMIMPINAN PARTISIPATIF (Sebuah Kajian Teoritis) - Sil Maria Ungirwalu (SOCIETAS, 2012)
Leadership plays a tremendous role, because it is a central figure who unites groups both inside and outside groups in leaders. In addition it is also a leader with expertise in influencing the followers with respect to the fulfillment of desire as well as the satisfaction of the followers. Now another leader should not be labeled as a good leader or not good, but the good aspects of our assessment focused on how one leader was memorable in certain situations. A participative leadership style played a role in which a leader is actively involved in group activities